MORELS OF WEST JAVA : DESCRIPTION AND POTENTIAL UTILIZATION - Ivan Permana Putra (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The genus Morchella or known as morels is one of the most popular edible mushrooms around the world. Information regarding the distribution and cultivation of this fungus are mostly from the temperate country. In Indonesia, to date only 2 reports of the distribution of this mushroom have been found, at Mount Rinjani West Nusa Tenggara (2012) and Mount Klabat Minahasa Utara (2019). Since then, there have been no report of this macrofungi in Indonesia. In 2020, local people ( the members of the Indonesian mushroom hunting community) shared the information about the appereance of Morchella at residence area near Mount Gede Pangrango, West Java. Morphological identification which completed by the description and macroscopic characterization confirmed the identity of the macrofungi as Morchella sp. Further observation using microscopic characters and / or DNA data needs to be done to confirm the taxonomic position to the species level in the future studies. This information adds to the recording of Morchella distribution and its potential use in Indonesia.Keywords: Inventory, Macrofungi, Indonesia, Morchella